Oceanic Plateau and Subduction Zone Jump: Two‐Dimensional Thermo‐Mechanical Modeling. Issue 7 (2nd July 2021) - Yan, Zhiyong; Chen, Lin; Xiong, Xiong; Wan, Bo; Xu, Houze
Abstract: Oceanic plateaus are characterized by overthickened crust and rheologically strong and chemically depleted mantle root with respect to normal oceanic lithosphere. The buoyant nature makes them have a great potential to resist subduction and initiate a new subduction zone behind the plateaus, yet the geodynamic process remains enigmatic. Here, we use 2D thermo‐mechanical modeling method to investigate the role of an oceanic plateau in subduction zone reorganization. We systematically examine the rheological strength and compositional density of oceanic plateau mantle and the size of oceanic plateau. Three distinct subduction styles are observed: (a) steep subduction without subduction zone reorganization, favored by a small‐sized (≤150 km) or lowly depleted oceanic plateau; (b) breakoff of subducting slab followed by flat‐slab subduction, which is conditional on a moderate‐sized (≥300 km) oceanic plateau with high degree depletion but relatively low strength; and (c) initiation of a new subduction zone behind the plateau (subduction zone jump), facilitated by a moderate‐sized oceanic plateau with a strongly depleted mantle root. The geodynamic results demonstrate that the overriding lithosphere undergoes a tectonic force switch from compression to tension in ∼5 Myr as the subduction zone is reorganized. This can be reflected in the crustal deformation of the overriding plate and used as an indicator to identify past subduction zone jumps. The spatial relationship predicted by the subduction zone jump models explains the Jurassic closure event of the accretion on southern Qiangtang at ∼175 Ma and the intraoceanic infant arc magmatism in the Meso‐Tethys at ∼165 Ma. Key Points: Different subduction styles controlled by the buoyancy and strength of the oceanic plateau, as well as its size Subduction zone jump occurs when the plateau has a strong rheological and highly depleted mantle root The continental tectonic force transformation systems can be used as an indicator to identify ancient subduction zone jumps